Calcium Sensitizers in Cardiac Surgery: Who, When, How and Why? - Orriach, J.L. G.; Ramirez-Fernandez, A.; Escalona-Belmonte, J.J.; Rubio-Navarro, M.; Cruz-Manas, J. (Current Vascular Pharmacology, 2018)
Inodilators are a heterogeneous group of drugs with vasodilatory and inotropic effects. The cardioprotective effect of levosimendan is multifactorial, but now research on levosimendan is focused on the organ-protective properties of this drug in different settings, the regimen that seems to provide the greatest cardiologic and systemic benefits is early administration of levosimendan. We try to answer four questions in this review, which type of patients need this drug? what is the best time to start with it? and the best way that we could give it and finally the reasons for use it.
Keywords: mechanisms